Prediction of flatwater kayaking performance - van Someren, K.; Howatson, G. (International Journal of Sports Physiology and Performance, 2008)
To determine the relative importance of anthropometric and physiological attributes for performance in the 1000-m, 500-m, and 200-m flatwater kayaking events. Methods: Eighteen competitive male kayakers completed performance trials over the 3 distances and a battery of anthropometric and physiological tests. Results: Performance times (mean ± SD) for 1000 m, 500 m, and 200 m were 262.56 ± 36.44 s, 122.10 ± 5.74 s, and 41.59 ± 2.12 s, respectively. Performance in all 3 events was correlated with a number of physiological parameters; in addition, 500-m and 200-m performance was correlated with upper body dimensions. 1000-m time was predicted by power output at lactate turnpoint expressed as a percentage of maximal aerobic power, work done in a 30-s ergometry test and work done in a 2-min ergometry test (adjusted R2 = 0.71, SEE = 5.72 s); 500-m time was predicted by work done and the fatigue index in a 30-s ergometry test, work done in a 2-min ergometry test, peak isometric and isokinetic function (adjusted R2 = 0.79, SEE = 2.49 s); 200-m time was predicted by chest circumference, humeral breadth, peak power, work done, and the fatigue index in a 30-s ergometry test (adjusted R2 = 0.71, SEE = 0.71 s). Conclusions: A number of physiological variables are correlated with performance in all events. 1000-m, 500-m, and 200-m times were predicted with a standard error of only 2.2%, 2.0%, and 1.7%, respectively.